2001
DOI: 10.1093/carcin/22.8.1201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of docosahexaenoic acid and eicosapentaenoic acid on androgen-mediated cell growth and gene expression in LNCaP prostate cancer cells

Abstract: There is some epidemiological support for a protective influence of omega-3 fatty acids against prostate cancer. We wanted to explore whether omega-3 polyunsaturated fatty acids such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) can affect androgen receptor function in prostate cancer cells. Our study showed that both DHA and EPA inhibit androgen-stimulated cell growth. Androgenic induction of prostate-specific antigen (PSA) protein was repressed by DHA and EPA in a dose-dependent manner. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 34 publications
6
31
0
Order By: Relevance
“…This inhibition occurred at concentrations not much greater than the ranges of the levels of PA and DHA in human serum, which are up to 30 and 12.7 mM, respectively (55,56). These results confirmed previous reports that DHA inhibits human prostate cancer cell pro- liferation (30,31,46,47). More importantly, our results indicate that PA could be a useful nutrient for dietary preventive and therapeutic approaches to human prostate cancer.…”
Section: Effects Of Rxr Ligands On the Proliferation Of Human Prostatsupporting
confidence: 91%
See 1 more Smart Citation
“…This inhibition occurred at concentrations not much greater than the ranges of the levels of PA and DHA in human serum, which are up to 30 and 12.7 mM, respectively (55,56). These results confirmed previous reports that DHA inhibits human prostate cancer cell pro- liferation (30,31,46,47). More importantly, our results indicate that PA could be a useful nutrient for dietary preventive and therapeutic approaches to human prostate cancer.…”
Section: Effects Of Rxr Ligands On the Proliferation Of Human Prostatsupporting
confidence: 91%
“…DHA can inhibit the growth of androgenresponsive LNCaP cells (46) and androgen-unresponsive PC-3 cells and DU-145 cells (47). Lampen, Meyer, and Nau (48) reported that PA and DHA enhanced the induction of CYP26A1 expression and retinoic acid oxidation by RAR ligands in cells.…”
mentioning
confidence: 99%
“…Thus, serum PSA level determination is used to aid diagnosis for prostate cancer and its levels are used for monitoring response to endocrine therapies. In the presence of androgen, expression of PSA is stimulated in prostate cells, including LNCaP cells (Horoszewicz et al, 1980;Chung et al, 2001). Measurement of PSA levels in medium from LNCaP cells transfected and purified by cell sorting showed that addition of R1881 resulted in a 25-fold increase in levels of secreted PSA in cells transfected with control Adeno (Figure 5a, lanes 3, 4).…”
Section: Stable Expression Of Plzf-ar Inhibits the Expression Of Andrmentioning
confidence: 99%
“…In vitro and in vivo animal data suggests that the balance of n-6 and marine-derived n-3 fatty acids affects the growth of prostate cancer. Linoleic acid (n-6) has been shown to exert a stimulatory effect on the growth of androgen-responsive (LNCaP) and androgenindependent (PC-3) human prostate cancer cell lines, whereas DHA and EPA (n-3) inhibit in vitro growth (1,2,5,6). In two prior animal feeding studies, n-3-based diets reduced the growth of s.c. DU-145 xenografts in nude mice when compared with n-6-based diets (3,4).…”
mentioning
confidence: 99%